Peran PPKn dalam Membentuk Karakter Mulia Siswa Kelas 2 SD Negeri 2 Pereng - Latia Anggun Paramita; Alfiani Nurjannah; Aulia Ratna Dewati; Endrise Septina Rawanoko (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Civic Education (PPKn) serves as an essential foundation for cultivating students’ moral character and citizenship values at the elementary level. This study examines the role of PPKn in shaping the noble character of Grade 2 students at SD Negeri 2 Pereng, identifies existing challenges in its implementation, and proposes strategies for improvement. Using a descriptive qualitative approach, data were collected through classroom observations and interviews with the Grade 2 teacher. The findings show that PPKn contributes significantly to developing students’ discipline, responsibility, cooperation, politeness, and patriotism through structured routines such as daily prayers, class duties, simple deliberation activities, and flag ceremonies. The teacher’s modeling and guidance further reinforce value internalization. However, limited audiovisual media, uneven literacy skills, and classroom management issues hinder optimal implementation. Effective solutions include simplifying learning materials, utilizing accessible visual media, strengthening teacher facilitation, and enhancing collaboration between school and parents. Overall, PPKn remains vital in supporting character development when supported by adequate strategies and consistent habituation.